THE DETERMINATION OF OPTIMUM CONDITION FOR THE SYNTHESIS OF ALKYL MONOETHANOLAMIDE FROM PALM KERNEL OIL - Hilyati Hilyati; Wuryaningsih Wuryaningsih; M. Nasir; Tasrif Tasrif; T. Beuna (Indonesian Journal of Chemistry, 2004)
Synthesis of alkyl monoethanolamide from palm kernel oil was done by two steps reaction that are esterification and amidation. The esterification, that is the reaction between palm kernel oil and methanol with mole ratio of 1:3 using acid catalyst (H2SO4) 4 % at temperature 60 OC for two hours, results in methyl ester palm kernel oil. The methyl ester product was produced by amidation reaction on any variation of time, temperature, catalyst, catalyst concentration and ratio of the reactan. The best result of the synthesis (amide conversion of 98.15 %) was obtained at temperature of 160 OC for 6 hours with mole ratio of methyl ester palm kernel oil to ethanol amine (ratio of the reactan) 1:1 using KOH catalyst 0.5 % and H2SO4 catalyst 0.5 %.